Nuclear Weapons in Britain's Policy towards France, 1960–1974 - Kris Stoddart (Diplomacy & Statecraft, 2007)
This article will attempt to draw attention to the Anglo–French nuclear weapons negotiations that ran alongside the British applications to join the EEC during the years 1960–1974. It suggests that the prospect of an entente nucléaire was an issue that played a unique role in the UK's negotiating strategy. It will argue that three successive Prime Minister's—Macmillan, Wilson and Heath—attempted to forge an agreement in the hope of overcoming French objections to Britain's entry, albeit for different reasons. All three were hampered by the “special nuclear relationship” with the Americans and this eventually precluded a mutually beneficial resolution.